2000
DOI: 10.1111/j.1365-2621.2000.tb10266.x
|View full text |Cite
|
Sign up to set email alerts
|

Short Chain Fatty Acids Alter HEp‐2 Cell Association and Invasion by Stationary Growth Phase Salmonella Typhimurium

Abstract: We examined the ability of stationary phase Salmonella typhimurium to adhere and invade cultured HEp-2 cells after growth in broth supplemented with acetate, propionate, butyrate, or a mixture of the three short chain fatty acids (SCFA). At pH 6, all concentrations, except 25 and 50 mM butyrate, reduced cell-association of S. typhimurium when compared to controls, while at pH 7 only 100 mM concentrations of acetate and butyrate reduced cell-association significantly. Invasion percentages were greater for S. ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…There were also indications that these S. Typhimurium responses were growth dependent, particularly in the presence of propionate and butyrate at pH 6.0, which reduced the growth rate considerably (341). However, when late-logarithmic-phase (12 h) and stationary-phase (18 h) S. Typhimurium cells were compared (342,343), all SCFAs reduced cell attachment at pH 6.0 and 7.0 but only marginally influenced invasion for late-log-phase cultures of Salmonella. The stationary-phase Salmonella cells exhibited reduced attachment only in the presence of SCFA at pH 6.0, while actual increases in invasion occurred for lower concentrations of acetate (342,343).…”
Section: Salmonella Virulence Response and Organic Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were also indications that these S. Typhimurium responses were growth dependent, particularly in the presence of propionate and butyrate at pH 6.0, which reduced the growth rate considerably (341). However, when late-logarithmic-phase (12 h) and stationary-phase (18 h) S. Typhimurium cells were compared (342,343), all SCFAs reduced cell attachment at pH 6.0 and 7.0 but only marginally influenced invasion for late-log-phase cultures of Salmonella. The stationary-phase Salmonella cells exhibited reduced attachment only in the presence of SCFA at pH 6.0, while actual increases in invasion occurred for lower concentrations of acetate (342,343).…”
Section: Salmonella Virulence Response and Organic Acidsmentioning
confidence: 99%
“…However, when late-logarithmic-phase (12 h) and stationary-phase (18 h) S. Typhimurium cells were compared (342,343), all SCFAs reduced cell attachment at pH 6.0 and 7.0 but only marginally influenced invasion for late-log-phase cultures of Salmonella. The stationary-phase Salmonella cells exhibited reduced attachment only in the presence of SCFA at pH 6.0, while actual increases in invasion occurred for lower concentrations of acetate (342,343). Van Immerseel et al, using avian intestinal and cecal epithelial cell lines, also observed increases in invasion of S. Enteritidis exposed to acetate for 4 h and decreases with propionate and butyrate (265,344).…”
Section: Salmonella Virulence Response and Organic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…can combat this stress by adaptation and acid tolerance response. [12,13,25] In the present study, the surface hydrophobicity of cells during logarithmic as well as stationary phase was evaluated by binding of congo red dye to bacterial cells. Mouse lethality determination revealed a 30-fold decrease in LD 50 of SCFA exposed cells (2.163 × 10 3 organisms/mouse) as compared to the normal cells (6.46 × 10 4 organisms/mouse).…”
Section: Resultsmentioning
confidence: 99%
“…[4] One of the potential stress conditions that can be encountered by the food-borne pathogens like Salmonella is their exposure to short chain fatty acids (SCFA), particularly acetate, propionate, and butyrate. [12,13] SCFA have also been observed to modulate the expression of Salmonella pathogenicity island invasion genes including hilA and invF. These acids can be found in concentrations as high as 190 mM in gastrointestinal ecosystems harboring extensive populations of fermentative anaerobic bacteria.…”
Section: Introductionmentioning
confidence: 99%